Evaluation of Bacillus Strains for Plant Growth Promotion and Predictability of Efficacy by In Vitro Physiological Traits - Rufus J. Akinrinlola; Gary Y. Yuen; Rhae A. Drijber; Anthony O. Adesemoye (International Journal of Microbiology)
Bacilli are commonly used as plant growth-promoting agents but can be limited in effectiveness to certain crop and soil environments. The objectives of this study were to (1) identify Bacillus strains that can be consistent in promoting the growth of corn, wheat, and soybean and (2) determine whether physiological traits expressed in vitro can be predictive of growth promotion efficacy/consistency and be used for selecting effective strains. Twelve Bacillus strains isolated from wheat rhizospheres were evaluated in greenhouse pot tests with nonsterile soil for their effects on the growth of corn, soybean, and wheat. The strains also were assessed in vitro for multiple physiological traits. All 12 strains increased corn growth significantly compared to the controls. The four most efficacious strains on corn—Bacillus megaterium R181, B. safensis R173, B. simplex R180, and Paenibacillus graminis R200—also increased the growth of soybean and wheat. No set of traits was a predictor of growth promotion efficacy. The number of traits expressed by a strain also was not an indicator of efficacy as strain R200 that was positive for only one trait showed high growth promotion efficacy. Effective strains can be identified through pot tests on multiple crop plants, but in vitro physiological assays are unreliable for strain selection.